Extracorporeal Shock Wave Lithotripsy (ESWL) for Kidney Stone Treatment in People with Hemophilia A - Ihsan, Rizki Muhammad; Romadhon, Yusuf Alam; Widodo, Dhito Putranto Dwi (Universitas Muhammadiyah Surakarta, 2024)
Acquired hemophilia A is a rare bleeding disorder that presents as gross hematuria, with or without an initiating factor such as stone or cancer in urinary tract. People with hemophilia may require some surgical procedures in their live. Surgery in patients with congenital or acquired coagulation defects has always been challenging and requires special care with a multidisciplinary approach. Extracorporeal Shock Wave Lithotripsy (ESWL) is a standard procedure performed in patients with kidney stones.